Selecting cadres: former members of the CCYL in the 19th Central Committee of CPC - Brona, Adrian (Asia in World Politics: Past, Present, and Future, 2021)
This chapter examines the role of Chinese Communist Youth League (CCYL) as breeding ground for crucial political leaders in China. Author shows the share of former affiliates of Central Committees CCYL in the 19th Central Committee of Communist Party of China (CC CPC) and compares with data from previous CCs. Analysis points out an insignificant correlation between engagement in CCYL and promotion into the CPC structures which shows the importance of the official youth organization of the CPC in the process of selecting the most powerful cadres of the party is overrated.